GASTRODUODENAL BLEEDINGS IN PATIENTS WITH THE PATHOLOGY OF CENTRAL NERVOUS SYSTEM - M. P. Korolev; A. V. Klimov; A. L. Ogloblin; I. S. Terehov; A. A. Sydikov; Sh. Kh. Doniyarov (Вестник хирургии имени И.И. Грекова)
The article presents a brief overview of local and foreign literature sources and reflects some of the issues of the etiology and pathogenesis of bleeding from the upper gastrointestinal tract in patients with acute vascular pathology of CNS and modern minimally invasive methods of hemostasis.